PEMBATASAN USIA PERNIKAHAN PERSPEKTIF KAIDAH MUWĀZANAH IZZUDDĪN IBN ABDISSALĀM - Muda'i, Syaiful; Amilatunnafi’ah (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2025)
Every individual has the right to establish a family through the institution of marriage. Children who grow and develop within the family structure are expected to become a high-quality and competitive generation for the nation. To realize this expectation, the government has enacted legislation setting a minimum age requirement for marriage. However, this regulation has sparked debate due to its perceived negative impacts and overlooked positive aspects. Using a qualitative descriptive-analytical method, this article examines the age restriction for marriage as stipulated in Law No. 16 of 2019, which amends Law No. 1 of 1974 on Marriage, through the lens of muwāzanah principles formulated by Izzuddīn ibn Abdissalām. The muwāzanah framework is essential as an analytical tool, serving as a parameter to guide decisions when facing conflicting or equally weighted benefits (mashālih) and harms (mafāsid) -ijtima’ baina al-mashalih wa al-mafāsid al-muta’aridlatain maupun al-mutasawiyatain-. The age limitation policy, grounded in the protection of children's rights, the prevention of various risks, and the preparation of a competent and competitive future generation, does not deviate from the tenets of Islamic law. On the contrary, it reinforces the core principles of the Sharia (al-asās al-tasyrīʿ al-khams).